Low Plasma Levels of Hyaluronic Acid Might Rule Out Sinusoidal Obstruction Syndrome after Hematopoietic Stem Cell Transplantation. (17th April 2023) - De Ramón Ortiz, Carmen; Justo Sanz, Raul; Beauverd, Yan; Humala, Karem; López de la Guia, Ana; De Paz, Raquel; Gasior, Mercedes; Gómez Prieto, Pilar; Fabra Urdiola, Marta; Canales Albendea, Miguel; Butta, Nora; Jiménez Yuste, Victor
Abstract : Background . Sinusoidal obstructive syndrome (SOS) is a potentially fatal complication secondary to hematopoietic stem cell transplant (HSCT) conditioning. Endothelial damage plasma biomarkers such as plasminogen activator inhibitor-1 (PAI-1), hyaluronic acid (HA), and vascular adhesion molecule-1 (VCAM1) represent potential diagnostic tools for SOS. Methods . We prospectively collected serial citrated blood samples (baseline, day 0, day 7, and day 14) in all adult patients undergoing HSCT at La Paz Hospital, Madrid. Samples were later analyzed by ELISA (enzyme-linked immunosorbent assay) for HA, VCAM1, and PAI-1 concentrations. Results . During sixteen months, we prospectively recruited 47 patients. Seven patients (14%) were diagnosed with SOS according to the EBMT criteria for SOS/VOD diagnosis and received treatment with defibrotide. Our study showed a statistically significant elevation of HA on day 7 in SOS patients, preceding clinical SOS diagnosis, with a sensitivity of 100%. Furthermore, we observed a significant increase of HA and VCAM1 levels on day 14. Regarding risk factors, we observed a statistically significant association between SOS diagnosis and the fact that patients received 3 or more previous lines of treatment before HSCT. Conclusions . The early significant increase in HA levels observed opens the door to a noninvasive peripheral blood test which could have the potential to improve diagnosis and facilitate prophylactic and therapeutic management of SOS before clinical/histological damage is established.